Empowering Bullying Victims Through Artistic Expression (L'autonomisation des victimes d'intimidation par l'expression artistique). Issue 1 (2nd January 2016) - Laffier, Jennifer
ABSTRACT: In order to help child victims of bullying, a greater understanding of the psychological empowerment process is needed, especially with regard to what type of activities support the development of empowerment. Artistic expression, an activity described previously as empowering, needed more attention with regard to its specific role toward greater empowerment. In order to explore the ways in which individuals can experience a sense of psychological empowerment from the artistic process the Nomological Network of Psychological Empowerment model was used in an exploratory case study. This study involved the data of four child victims of bullying involved in a 14-week art therapy program in an elementary school in Ontario, Canada. Various data sources, such as pre and post surveys, artworks, clients' reflection notes, and the therapist's notes, were examined to uncover any experiences of psychological empowerment. Qualitative content analysis revealed that artistic expression in art therapy provided experiences of psychological empowerment in a myriad of ways and as a cyclical process leading to greater mental health for the participants. Thus, art therapy should be considered as an intervention method for children experiencing bullying. Additionally, researchers should further investigate the empowerment process in longitudinal studies to determine the empowerment process over time.